Unravelling the interplay between social support and recreational sports participation among academic staff - Zulkifli, Muaz Hamdi; Abdul Majeed, Hasmiza; Rajli, Mohammad Adzly (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study investigates the relationship between social support from family, friends, and significant others and recreational sports participation among academic staff at UiTM Seremban 3. By addressing the research gap concerning socio-cultural factors in the Malaysian context, the study identifies support levels and engagement duration to understand how interpersonal relationships influence physical activity. The findings aim to inform targeted wellness strategies and foster a sustainable culture of active living within the academic community.